Uji Kerentanan Aedes aegypti terhadap Malation, Permetrin, dan Bendiokarb di Kelurahan Tangkerang Timur Kecamatan Tenayan Raya, Pekanbaru - Elva Susanty; Suri Dwi Lesmana; Mislindawati Mislindawati; Aditya Fikri Aulia; Akhwani Zuqni; Muhammad Naufal Atsila (Fakultas Kedokteran Universitas Riau, 2024)
Insecticide resistant of Aedes aegypti populations is one of the main problems in controlling dengue hemorrhagic fever vectors because it will produce resistant offspring. This study aimed to determine the insecticide susceptibilty status of Ae. aegypti to 5% malathion, 0,75% permethrin, and 0,1% bendiocarb in Tangkerang Timur Village, Tenayan Raya District, Pekanbaru. This study is a descriptive observational study with a cross-sectional design. The resistance test method in this study was the World Health Organization (WHO) susceptibility test method with impregnated paper (5% malation, 0,75% permethrin, and 0,1% bendiocarb). The larval that were reared into adult mosquitoes were collected from 100 houses in Tangkerang Timur Village. Total adult mosquitoes aged 3-5 days tested in this study were 100 mosquitoes. The test mosquitoes were exposed to impregnated paper for 1 hour and the number of knock down mosquitoes was counted. Mosquito mortality was counted after 24 hours. The results of the susceptibility test in this study showed the mortality of Ae. aegypti to 5% malathion, 0,75% permethrin, and 0,1% bendiocarb were 100%, 85%, and 3.75%. The results of this study indicated that Ae. Aegypti has been resistant to 0,75% permethrin and 0,1% bendiocarb and susceptible to 5% malathion.